2019
DOI: 10.1038/s41467-019-09589-w
|View full text |Cite
|
Sign up to set email alerts
|

A dynamic thermoregulatory material inspired by squid skin

Abstract: Effective thermal management is critical for the operation of many modern technologies, such as electronic circuits, smart clothing, and building environment control systems. By leveraging the static infrared-reflecting design of the space blanket and drawing inspiration from the dynamic color-changing ability of squid skin, we have developed a composite material with tunable thermoregulatory properties. Our material demonstrates an on/off switching ratio of ~25 for the transmittance, regulates a heat flux of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
113
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 134 publications
(120 citation statements)
references
References 38 publications
0
113
0
Order By: Relevance
“…Within this context, devices or systems that can potentially manipulate light across both the visible (400–740 nm) and IR (740 nm to 15 µm) spectral regions remain quite rare. To date, relatively few classes of these technologies have been reported, such as thermochromic phase‐change materials,17–20 electrochromic devices,21–23 IR‐reflecting platforms,24,25 and reconfigurable soft machines9 (see Table S1, Supporting Information), and they have featured drawbacks that include a limited degree of spectral modulation, impractical actuation requirements, poor stability to repeated actuation, slow response times, and/or complicated fabrication 9,17–25. Indeed, the engineering of devices and systems with tandem adaptive functionality across a broad spectral window (i.e., encompassing the visible, near‐IR, short‐wavelength IR, mid‐wavelength IR, and long‐wavelength IR) has proven challenging, in part because of the order of magnitude difference in the length scales associated with the propagation of visible and long‐wavelength IR light.…”
Section: Figurementioning
confidence: 99%
“…Within this context, devices or systems that can potentially manipulate light across both the visible (400–740 nm) and IR (740 nm to 15 µm) spectral regions remain quite rare. To date, relatively few classes of these technologies have been reported, such as thermochromic phase‐change materials,17–20 electrochromic devices,21–23 IR‐reflecting platforms,24,25 and reconfigurable soft machines9 (see Table S1, Supporting Information), and they have featured drawbacks that include a limited degree of spectral modulation, impractical actuation requirements, poor stability to repeated actuation, slow response times, and/or complicated fabrication 9,17–25. Indeed, the engineering of devices and systems with tandem adaptive functionality across a broad spectral window (i.e., encompassing the visible, near‐IR, short‐wavelength IR, mid‐wavelength IR, and long‐wavelength IR) has proven challenging, in part because of the order of magnitude difference in the length scales associated with the propagation of visible and long‐wavelength IR light.…”
Section: Figurementioning
confidence: 99%
“…Reproduced with permission. [ 102 ] Copyright 2019, Nature Publishing Group. B) Schematic and confocal fluorescent microscopy images of the dynamical IR‐gating textile switching between the open state (tight yarn) to close state (loose yarn) by the temperature and humidity, and a photograph of a fabric knitted from the bimorph fibers.…”
Section: Advanced Strategiesmentioning
confidence: 99%
“…[100] In nature, creatures such elytra of longhorn beetles and the blue skin of the mandrill possess special structures on their skins to decrease their skin temperature to adapt to a hot environment. [101][102][103][104] However, it is challenging to simultaneously effective control the thermal emission in the IR spectrum while maintaining substantial visible colors of textiles. This is because most organic chemical bonds in textiles or dyes strongly absorb the human-body thermal radiation, leading to low transmittance and high emissivity of the textiles.…”
Section: Colored Textilementioning
confidence: 99%
“…When comparing different conventional blankets, e.g., space blankets, bubble wrap, blizzard blankets, ambulance blankets and ready heat blankets, Zasa et al observed that all tested tools significantly reduced heat loss but could not completely compensate for the temperature deficit [4]. Contrarily, Leung et al observed an increase in skin temperature of approximately 1 • C, when measured with a thermal camera aimed at a forearm wrapped in a rescue blanket [5]. Allen et al performed an experimental study on a fluid torso model and observed diminished temperature loss when applying passive warming devices such as space blankets [6].…”
Section: Introductionmentioning
confidence: 99%